Suicidal ideation and suicide attempt among pregnant adolescent girls in Ghana: a cross-sectional study - Kwaku Oppong Asante; Emmanuel Nii-Boye Quarshie; Erica Danfrekua Dickson; Sandra Naa-Shasha Quarshie; Sophia Ewuenye Adwoa Kpebu (General Psychiatry)
Background Globally, suicide is the third leading cause of death among girls aged 15–19 years. However, there is a growing concern that suicide research has paid little attention to pregnant adolescent girls, particularly in low-income and middle-income countries, including Ghana, where nearly one in seven adolescents experiences (unwanted) pregnancy.Aims To assess the prevalence and correlates of suicidal ideation and suicide attempt and the self-reported reasons for attempted suicide among pregnant adolescent girls in Ghana.Methods We collected cross-sectional data (between August 2022 and December 2023) using structured anonymous questionnaires from a sample of 449 pregnant adolescent girls (aged 14–19 years) drawn from the three geographical zones of Ghana. We applied bivariable and multivariable analysis techniques to the data.Results Overall, 28.51% (95% confidence interval (CI) 24.37% to 32.93%) reported suicidal ideation, and 18.04% (95% CI 14.59% to 21.91%) reported suicide attempt during the current pregnancy. Participants who reported attempted suicide endorsed more interpersonal reasons (eg, to communicate distress, to seek help or to influence others) than intrapersonal reasons for their attempted suicide. In the final adjusted logistic regression models, food insecurity (adjusted odds ratio (aOR)=2.69; 95% CI 1.34 to 5.41; p=0.005) was uniquely associated with increased odds of suicidal ideation. Adverse childhood experiences (aOR=3.04; 95% CI 1.33 to 6.97; p=0.008), history of attempted suicide before current pregnancy (aOR=3.47; 95% CI 1.27 to 9.47; p=0.0.015) and depression (measured by the 5-item World Health Organization Well-Being Index; aOR=0.31; 95% CI 0.12 to 0.77; p=0.012) were uniquely associated with increased odds of suicide attempt. Five variables were commonly associated with increased odds of both suicidal ideation and suicide attempt: conflict with parents, alcohol use, pregnancy-related anxiety, history of attempted suicide and intimate partner violence. While being in junior high school was uniquely associated with reduced odds of suicidal ideation, intimate partner’s acceptance of paternity was commonly associated with reduced odds of both suicidal ideation and suicide attempt.Conclusions Although the prevalence estimates of suicidal ideation and suicide attempt in this study are comparable with known rates among non-pregnant adolescent girls in Ghana, additional research is needed to nuance our understanding of the correlates identified in this study. The evidence also highlights a need for both routine antepartum primary care mental health screening for suicidality and related risks and targeted prevention and intervention programmes.